DEVELOPMENT OF ENVIRONMENTAL CARE-BASED CURRICULUM IN IMPROVING CHARACTER EDUCATION IN ELEMENTARY SCHOOLS - Elsi Oktarina; Ana Fitrotun Nisa (UNIVERSITAS PAKUAN, 2021)
This study aims to develop a curriculum based on environmental care in improving character education in primary school. This research uses a qualitative approach. The research subjects were teachers and primary school students. Data collection techiques using observation and interviews. The data analysis technique was using a qualitative descriptive analysis technique. Forms of curriculum development based on environmental care in improving character education in primary school, among others: As an attitude an actions that always strive to prevent damage to the natural environment around it and develop efforts to repair natural damage that has occurred bypreserving the environment disposing of garbage in its place and do reforestation the character of caring for the environment is an attitude that is owned by someone who strives to improve and manage the surrounding environment properly so that the environment can be continucusly without damaging it is condition, as well as and maintaining and preserving so that there are sustainable benefits.